Self-Reported Appetite and Intake Adequacy In Patients With Non-dialysis Chronic Kidney Disease - Maria Chan; John Kelly; Marijka Batterham; Linda Tapsell (The Korean Society of Nephrology, 2012)
Subjective assessment of appetite using the Appetite and Diet Assessment Tool (ADAT) with 5-point Likert scales, (1) very good, (2) good, (3) fair, (4) poor and (5) very poor has been useful in screening patients for suboptimal intake and predicting hospitalization rate in patients on maintenance dialysis. The purpose of this study was to examine the relationships of self-reported appetite score and the estimated energy and protein intakes in a cohort of ESKD patients attending the pre-dialysis assessment clinic. As part of the routine assessment, patients were asked to rate their appetite using the ADAT; their dietary intake was assessed by the renal dietitian using a structured diet history method and computer software analysis. Of the 205 patient assessed, 60.5% were male; mean age was 65.7±13.6 years and mean GFR was 17.0±4.2 ml/min. 39.5% were rated as malnourished (SGA score B&C). 69.8% of patients rated their appetite as (1) very good or (2) good, whereas 30.2% rated their appetite as (3) fair or (4) poor or (5) very poor. Intakes of >25 kcal/kg IBW/d and >0.75 g/Kg IBW/d were considered adequate for energy and protein respectively. The mean ±SD of energy and protein intakes rated by the appetite score are as follow: Appetite score 1+2 (Good) 3+4+5(Reduced) P value Energy kcal/kgIBW/d 24.4±6.7 20.7±6.6 < 0.0001 Protein g/kgIBW/d 1.21±0.42 1.00±0.43 < 0.004 The positive predictive value (95%CI) of appetite rating for energy and protein were 0.37 (0.32-0.41) and 0.90 (0.86-0.93) respectively. In conclusion, while self-reported appetite scores were useful in ranking energy and protein intakes, subjective reporting of good appetite was associated with adequate protein but not energy intake. Report of a good appetite does not always mean adequate intake in non-dialysis ESKD patients with high symptom burden.